The Role of University Curricula in Shaping Students’ Political Awareness and Consolidating Democratic Values: A Field Sociological Study (The International Journal of Educational Sciences and Arts, 2026)
This study examines the role of university curricula in shaping students’ political awareness and promoting democratic values, with particular attention to students’ own perceptions of this role. It also investigates whether the curriculum may contain implicit or hidden objectives that could, either intentionally or unintentionally, differ from the university’s democratic mission.In this context, the study explores how university courses and academic programs contribute to the development of democratic values and political consciousness among students. The research focuses on youth at Ibn Zohr University in Morocco. The study sample consists of 300 graduate students (Master’s and PhD) from different faculties across the university.The analysis is structured around three main dimensions. The first examines the extent to which university curricula contribute to the promotion of democratic values. The second analyzes the role of curricula in strengthening students’ political culture and enhancing their political awareness. The third explores the hidden dimensions of the curriculum and assesses their alignment with the university’s democratic function.The findings suggest that the curriculum at Ibn Zohr University still faces several limitations in fulfilling its democratic and formative roles. These limitations partly explain the declining level of confidence among students in the curriculum’s ability to support democratic engagement. Many respondents consider the current curriculum insufficient for preparing graduates who are aware of their rights and responsibilities and capable of participating actively and responsibly in public life.
Keywords: University Curriculum; Political Awareness; Democratic Values; Hidden Curriculum